Gross Anatomical Variations of Placental Disc in Healthy Pregnancies among Local Population - Aneeqa Chughtai, Yasmeen Bashir, Saira Munawar, Humara Gul, Zaffar Iqbal Malik, Shamsa Mohsin (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The placental variations from one another based on factors such as organ division, fetal membrane insertion, and the location of implantation has already been distinguished. Our primary goal is to identify any gross anatomical variations of placentae in the local Pakistani female population who give birth vaginally in accordance with the pathological findings. Objective: To find out the gross anatomical variants of placental disc in the Pakistani population. Methodology: Hundred placentae were obtained by simple random sampling (probability) from the normal deliveries. Detailed gross morphology was carried out to find out the anatomical variants with values ≤ 5%. Analysis of data was done by using SPSS 20. Results: Single lobed placentae were present up to 95%. Round shaped discs were present in up to 70% cases. 2% placentae with diameter between 220 to 229mm and 5% between 140 to 149mm were present as variants. Soft consistency presents in 99% of placentae. Chorionic vessels numbered 6 to 8 among 4% and 2% respectively. Presence of sub-amnionic cysts, subchorionic hemorrhage and white infarcts in 4%, 2% and 2% respectively as variants. Number of cotyledons as among every 2% with 24, 26 and 27 respectively and the cotyledons size as among 5%, 3% to be 2 to 2.5cm and 4.6 to 5.0 cm respectively were present as variants. Conclusion: Both quantitative and qualitative variables exist in normal term placentae among local women in Pakistan. The presence of anatomical variants in the placental discs discerns non-pathological from other pathological events with poor outcome. Keywords: Chorionic, Cotyledon, Placenta.